Homoeopathy A Holistic Approach as Palliative Medicine (Homoeopathy for All, 2025)
Palliation is temporary relief of  symptom of diseases. Palliation  is the approach of preventing or  treating symptoms and side effects  of disease and treatment. Palliation  should not only on physical pain but  also emotional, social, and spiritual  background that arise from illness.  It does not depend on the patient’s  prognosis and can be provided at  any stage of a serious or chronic  illness. WHO recognised palliative  care as a speciality dedicated  exclusively to the relief of suffering  and improving the Quality of Life of  the patient with life limiting illness.  Kerala was the first state to take the  initiative and implement a Palliative  Care Policy and decided to include  homoeopathy in the spectrum of  Palliative Care. Homeopathy is  capable of bringing the immune  system back to its original strength  potential. The curability of any  condition depends upon the vitality  of person to restore the strength of  the immune system. If the health  a person is more compromised  due to long term illness, then less  will be the expressions through  symptomatology.
Keywords: Homoeopathy; palliative care; holistic medicine; symptom relief; end-of-life care; future perspectives